The Amphibian Ear - Wever, Ernest Glen, 1902- (Book collections on Project MUSE., 1985)
Professor Wever studies the structure of the ear and its functioning as a receptor of sounds in all amphibian species (139) for which living representatives could be obtainedOriginally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.